Effect of Gd3+substitution on proton relaxation and magnetic hyperthermia efficiency of cobalt ferrite nanoparticles - Jaison D.; Meher Abhinav E.; Gangwar A.; Nand Kishore P.; Chandrasekaran G.; Mothilal M. (My University, 2025)
In this study, Gadolinium substituted Cobalt Ferrite nanoparticles (CoFe2-xGdxO4, 0 ≤ x ≤ 0.4) were prepared via hydrothermal route using triethylamine as reducing agent at 180°C for 12 h. X-ray diffraction studies revealed the single phase cubic spinel structure for both Cobalt ferrite (CF) and Gadolinium substituted Cobalt Ferrite (CFG) nanoparticles (x ≤ 0.24). An increase in the Specific absorption rate (SAR) was observed with increase in Gd concentration. Further with increase in the molar concentration (x > 0.24), gadolinium hydroxide was observed as the secondary phase, which was also confirmed by the Gd-O stretching vibrations observed in Fourier transform Infrared spectroscopy. The evolution of Gadolinium hydroxide showed a strong influence in the relaxivity (r 1) and hyperthermia potential. Field emission scanning electron microscopy revealed that CF and CFG (x ≤ 0.24) nanoparticles were spherical in nature with particle size ranging from 10 to 25 nm, whereas the particle size increases above 30 nm for CFG (0.3 ≤ x ≤ 0.4) nanoparticles along with the presence of columnar shaped particles. Magnetic measurements confirmed the pseudo single domain, ferri-magnetic nature of CF and CFG nanoparticles. The magnetization data revealed a change in direction of magnetization towards easy axis with increasing Gd concentration. The orientation of magnetization direction towards easy axis had induced change in the hyperthermia potential. Proton relaxation studies of CF and CFG nanoparticles revealed that there is a strong interaction between the relaxivities r 1 and r 2. The specific absorption rate of CF and CFG nanoparticles were observed to be in the range from 91.49 W g-1 to 232.17 W g-1 at applied Hf of 4.19 ° 109 Am-1 s-1. © 2020 The Author(s). Published by IOP Publishing Ltd.